Proximate and Ecological Analysis of Mangrove Crab (Scylla serrata) in the Maro River Estuary Mangrove Ecosystem - Masiyah, Siti; Monika, Surya Nova (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
The research was conducted for 3 months, namely August-October 2020. At the mouth of the Maro River, the Nusantara Fisheries Port, Merauke Regency with the aim of knowing the proximate content of mangrove crabs and the ecology in the study area. This research is a purposive sampling method, which is sampling intentionally in accordance with the necessary conditions (characteristics, characteristics, criteria) so that it can represent the entire population. For the sample, the proximate analysis was carried out at the Testing Laboratory of the Research Institute for Brackish Water Aquaculture and Fishery Extension and for COD and BOD analysis, it was carried out at UNS Solo. The analysis results obtained for proximate analysis in 100 grams of mud crab meat with the gravimetric method obtained values for ash content of 50.49%, water content of 3.51%, fat content of 0%, protein content of 35.18% and fiber content of 10.01%. ecology, while for analysis COD and BOD obtained 2.3 – 2.8 mg/l while for analysis COD obtained 4.98 -6.38 mg/l research area is very suitable for the survival of mangrove crabs. The researcher will provide benefits to the relevant agencies in managing the potential of mangrove crabs and as information about proximate users of mangrove crabs in Merauke Regency.